A preliminary investigation into the potential eﬀect of Artemisia afra on growth and disease resistance in sub-adults of Oreochromis mossambicus - Moyo, N. A. G.; Mbokane, E. M (Aquaculture, 2018)
This study investigated the potential of Artemisia afra on growth and disease resistance in Oreochromis mossambicus. Phytochemical analysis of A. afra was also undertaken. Five A. afra-based diets designated as D1, D2, D3, D4 and D5 were formulated and randomly fed to triplicate groups of 45 ﬁsh (32.5 ± 1g). At the end of feeding, Food Conversion Ratio and Speciﬁc Growth Rate values were not signiﬁcantly diﬀerent (F15,4 = 0.6, p > 0.05; F15,4 = 0.45, p > 0.05, respectively) between D1 and the other diets. Weight gain and feed intake were higher in D1, D2 and D3 than in D4 and D5, but no signiﬁcant diﬀerence (ANOVA, p > 0.05) was found between treatments. This suggests that safe dosages were used. Phagocytosis and lysozyme activity were higher in ﬁsh fed D4 and D5 than those fed D1 and the other diets. White blood cells were also higher in ﬁsh fed the A. afra-based diets. To test for disease resistance, ﬁsh from each dietary treatment were injected with varying concentrations (0, 1 × 106 cfu, 1.5 × 106 cfu, 3 × 106 cfu, 4 × 106 cfu mL˗1) ofAeromonas hydrophila. Relative percentage survivalandthesurvival rateofO.mossambicuswerehigherin ﬁshfedD4andD5,indicatingthatthe use of A. afra-based diets enhanced immunity of O. mossambicus. This is because A. afra contained a number of biologically active compounds that act as immunostimulants. High levels of total polyphenol (70.32 ± 3.5 mg100 g˗1), total phenols (88.65 ± 5.32 mg 100 g˗1), total ﬂavonoids (181.5 ± 4.13 mg g˗1) and alkaloids (29.63 ± 3.58 g kg˗1) were recorded in A. afra.
Article published in the Aquaculture 482 (2018) 197–202
Keywords: Fish health; Medicinal plants; Infectious diseases; Survival rate; Aquaculture; Aquaculture -- Africa, Sub Saharan